Sosio Economic: Forms of Community Welfare Based on Islamic Economic Principles - Fuad, Yahya; Aisyul Hana, Ubaid; Azizah, Zumrotul (TAWAZUN: Journal of Sharia Economic Law, 2024)
This study explores the application of Islamic economic principles in enhancing societal welfare, focusing on economic justice, the prohibition of riba (interest) and gharar (excessive uncertainty), and the obligation of wealth sharing. The primary objective of this research is to analyze the effectiveness of these principles in the modern context and their impact on social and economic welfare. The methodology includes a review of recent literature and secondary data analysis from various reports and case studies related to Islamic economics. The findings indicate that economic justice principles, through wealth redistribution mechanisms such as zakat, significantly reduce income inequality and improve the quality of life for the less fortunate. Islamic banking, by avoiding interest and applying profit-sharing principles, contributes to economic stability and financial inclusion, while mitigating systemic risks often associated with conventional banking systems. Furthermore, effective and transparent management of zakat and waqf has supported social development through various initiatives in education, healthcare, and social infrastructure. However, challenges include the lack of uniform international standards for Islamic financial institutions and the need for regulatory reforms. On the other hand, there are significant opportunities through innovations in Islamic financial products and international cooperation to strengthen the financial sector and enhance societal welfare. In conclusion, Islamic economic principles can make a meaningful contribution to societal welfare if implemented effectively with adequate regulatory support and transparency.Keyword: Islamic economics, social welfare, zakat, alms, usury, distribution of wealth